(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
At present, the attention of linguists is concentrated mainly on the Paralinguistic means of biological origin, but functionally used in communication. Paralinguistic phenomena, or paralinguisms, usually include a property sound phonation, as well as facial expressions, gestures and other expressive movements, accompanying speech utterance and bearing an additional to its content information. Phonation from the Greek phōnē - sound, voice.